Asegi Stories : Cherokee Queer and Two-Spirit Memory - Driskill, Qwo-Li (Book collections on Project MUSE., 2016)
"The book focuses on the concept of asegi stories--stories that revise and revive Cherokee cultural memories of same-sex relationships and non-binary gender systems. It is the first full-length work of scholarship to develop a tribally specific Indigenous queer/two-spirit critique, providing a Cherokee 2GLBTQ lens from which to interpret the past, understand our present, and imagine decolonial futures"--Provided by publisher.